2017
DOI: 10.12659/ajcr.902633
|View full text |Cite
|
Sign up to set email alerts
|

A Case with Recurrent Free-Floating Ball Thrombi in Left Atrium

Abstract: Patient: Female, 74Final Diagnosis: Left atrial ball thrombusSymptoms: Abdominal discomfort • dyspneaMedication: —Clinical Procedure: —Specialty: CardiologyObjective:Rare diseaseBackground:A free-floating ball thrombus in the left atrium is a rare clinical condition. However, the diagnosis of this condition has been facilitated by the advent and development of echocardiography and multi-detector row computed tomography (MDCT) and several cases have been reported.Case Report:We report a case of a 75-year-old wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Although similar cases were abundantly described [411], to the best of our knowledge, a free-floating ball-shaped thrombus with coexisting biatrial appendage thrombi imaged on echocardiography was the first reported case. In the only relevant report, Yoshioka et al introduced a case of left atrial ball-shaped thrombus in conjunction with left atrial appendage thrombus [11]. For our case, in addition, other than anatomical and functional abnormalities of the left atrium, a low-output state associated with stenotic prosthetic valve might facilitate thrombosis in the appendages.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Although similar cases were abundantly described [411], to the best of our knowledge, a free-floating ball-shaped thrombus with coexisting biatrial appendage thrombi imaged on echocardiography was the first reported case. In the only relevant report, Yoshioka et al introduced a case of left atrial ball-shaped thrombus in conjunction with left atrial appendage thrombus [11]. For our case, in addition, other than anatomical and functional abnormalities of the left atrium, a low-output state associated with stenotic prosthetic valve might facilitate thrombosis in the appendages.…”
Section: Discussionmentioning
confidence: 83%
“…Free-floating ball-shaped thrombus in the left atrium is a rare finding among patients with mitral valve disease with or without a history of valve replacement surgery [38]. This type of thrombus was reported to form in the absence of valve disease and also to recur despite adequate anticoagulation [10, 11]. The precise mechanism behind the occurrence of a free-floating ball-shaped thrombus remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is speculated that a fixed thrombus initially forms in the left atrial appendage or the left atrial wall [6] . Afterwards, it grows into a round shape, followed by disconnection of the pedicle between the thrombus and the atrial wall [7] . Wall-adherent thrombi can detach and float freely [8] .…”
Section: Discussionmentioning
confidence: 99%